Productive Waqf Accounting: A Systematic Literature Review of Financial Recording and Reporting Models - Wali Saputra (Jurnal Ilmiah Literasi Indonesia, 2025)
The objective of this research is to conduct a systematic examination of the existing literature pertaining to the accounting and financial reporting frameworks associated with productive waqf. The productive waqf, recognized as a pivotal instrument within Islamic social finance, necessitates an accounting system that is both accountable and transparent to facilitate the optimal management of assets and funds, in adherence to Sharia principles. The methodological approach employed is a Systematic Literature Review (SLR) encompassing scholarly publications from the years 2010 to 2025, sourced from the Scopus, Google Scholar, and DOAJ databases. The findings of this inquiry indicate that the practices associated with productive waqf accounting remain non-standardized on a global scale. Various accounting models identified include fund accounting methodologies, activity-based reporting frameworks, and the integration of social reporting. Nonetheless, the implementation of these models is still constrained and adversely influenced by limited human resource capabilities and a deficiency in specific regulatory frameworks. Furthermore, the study identifies significant potential for the utilization of information technologies, such as blockchain and Sharia-compliant ERP systems, in enhancing the transparency of financial reporting. This research advocates for the formulation of more comprehensive accounting standards for productive waqf, the enhancement of nazhir competencies, as well as the digitization of waqf financial reporting processes. These findings contribute to the establishment of both theoretical and practical foundations aimed at fostering more professional, reliable, and sustainable governance of productive waqf.